On the multiple dimensions of youth labour markets: A guide to the KOF Youth Labour Market Index - Ursula Renold; Thomas Bolli; Maria Esther Egg; Filippo Pusterla (ETH Zurich, KOF Swiss Economic Institute, 2014)
This report describes the development of the KOF Youth Labour Market Index (KOF YLM Index), a tool that allows to compare the labour market situation of youth across countries. This project, developed by the Research Division Education System, aims to disentangle problematic defined as "youth paradox", i.e. the fact that in these days the access to education reaches levels never reached before but even though increasingly problems in the integration process of youth into the labour market are observable. Our approach is multidimensional: the basic idea is that a single indicator (e.g. the widespread used unemployment rate) does not provide sufficient information for a comprehensive analysis. In order to foster multidimensionality we thus select twelve indicators that describe the labour market from different perspectives. The data for these indicators are collected from various international institutions and cover up to 178 countries for the time period between 1991 to 2012. On the basis of these indicators we first develop the KOF YLM Index. The evolution of this index over time, as well as the representation of the indicator set in a spider web, are displayed in a specific web application. A part of this report illustrates the usefulness of the web application in a detailed descriptive analysis of selected European countries. Beside of illustrating the developments in Europe's largest countries, a particular focus lies on countries that have struggled most during the Great Recession. The heterogeneity of the developments over time of the KOF YLM Index components highlights the relevance of accounting for the multidimensional approach of the youth labour market. This tool, which is available at at http://kof.ethz.ch/de/indikatoren/, is part of a widespread research project aiming to identify the connections between the typology of education system and the situation on the labour market for young aged 15 to 24 years.
Keywords: 330; Jugendarbeitslosigkeit; Index; Indexberechnung